2019
DOI: 10.3389/fmicb.2018.03340
|View full text |Cite
|
Sign up to set email alerts
|

Cultivated Human Vaginal Microbiome Communities Impact Zika and Herpes Simplex Virus Replication in ex vivo Vaginal Mucosal Cultures

Abstract: The human vaginal microbiome (VMB) is a complex bacterial community that interacts closely with vaginal epithelial cells (VECs) impacting the mucosal phenotype and its responses to pathogenic insults. The VMB and VEC relationship includes nutrient exchange and regulation of signaling molecules that controls numerous host functions and defends against invading pathogens. To better understand infection and replication of sexually transmitted viral pathogens in the human vaginal mucosa we used our ex vivo VEC mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 57 publications
(101 reference statements)
4
24
0
Order By: Relevance
“…Primary and immortalized cell lines have been created previously by our lab using nasal and vaginal mucosa [ 27 , 28 , 29 ]. To create esophageal cell lines, immortalized cell lines were derived from human esophageal mucosal biopsies transformed with human papilloma virus E6E7.…”
Section: Methodsmentioning
confidence: 99%
“…Primary and immortalized cell lines have been created previously by our lab using nasal and vaginal mucosa [ 27 , 28 , 29 ]. To create esophageal cell lines, immortalized cell lines were derived from human esophageal mucosal biopsies transformed with human papilloma virus E6E7.…”
Section: Methodsmentioning
confidence: 99%
“…Cases of ZIKV/HSV-2 coinfections have already been described in pregnancy in several prospective studies [ 52 ]. In addition, one comparative study showed that HSV-2 infection induces cytotoxic and inflammatory effects in the sterile vaginal system, while ZIKV infection alone does not result in obvious epithelial destruction [ 152 ].…”
Section: Human Latent Virus (Hlv) Selection With Common Interests In Czsmentioning
confidence: 99%
“…HSV-2 induces immunomodulation and proinflammatory cytokine production (including interleukins IL-8 and IL1β) making it an ideal antagonistic or synergetic partner in enhancing ZIKV pathogenicity in pregnancy ( Figure 4 : Pathogenesis changes) [ 152 ]. ZIKV RNA accumulation in the placenta of pregnant C57BL/6 mice exposed to HSV-2 at day E8.5 (equivalent to the first trimester in humans) and then infected with ZIKV at day E11.5 was significantly higher compared to pregnant mice monoinfected with ZIKV alone (Replication promotion).…”
Section: Human Latent Virus (Hlv) Selection With Common Interests In Czsmentioning
confidence: 99%
“…In humans, ZIKV RNA was identified in the oocytes, but not in follicular fluid or cumulus cells, of a woman infected with ZIKV undergoing in vitro fertilization (IVF) (42). In addition, ZIKV has been shown to infect cells of other female reproductive organs, including cultured endometrial stromal cells and vaginal epithelial cells collected from humans (43,44). While Zika infection appeared cytotoxic in endometrial cells, it did not induce significant cytotoxicity or inflammation in the vaginal epithelial cells (43,44).…”
Section: Zikamentioning
confidence: 99%